Comparison of the effects of fasting morning, fasting evening and fed bedtime administration of tenatoprazole on intragastric pH in healthy volunteers: a randomized three‐way crossover study - THOMSON, A. B. R.; COHEN, P.; FICHEUX, H.; FIORENTINI, P.; DOMAGALA, F.; HOMERIN, M.; TACCOEN, A. (Alimentary pharmacology & therapeutics, 2006)
Background  The effectiveness of proton pump inhibitors is influenced by meals and administration time. Aim  To compare the effects on intragastric acidity of times of dosing of tenatoprazole, a novel imidazopyridine‐based proton pump inhibitor with a prolonged plasma half‐life. Methods  This randomized three‐period crossover study included 12 Helicobacter pylori‐negative healthy subjects, who received tenatoprazole 40 mg either fasting at 7.00 am, fasting at 7.00 pm or fed at 9.30 pm for 7 days, with a 2‐week washout between periods. Twenty‐four hour intragastric pH was monitored on day 7 of each period. Results  On day 7, median 24‐h pH was 4.7, 5.1 and 4.7 after breakfast, dinner and bedtime dosing, respectively (P = 0.11), whereas night‐time pH was 4.2, 5.0 and 4.4 (P = 0.13). The mean 24‐h percentage of time over pH 4 was 62, 72 and 64 after breakfast, dinner and bedtime dosing, respectively (N.S.), and 54, 68 and 56 during night‐time (P = 0.06). Nocturnal acid breakthrough incidence decreased from 100% at baseline to 83%, 55% and 75% after 7.00 am, 7.00 pm and 9.30 pm dosing, respectively (P = 0.18), and its mean duration dropped from 6.2 to 2.8, 1.0 and 2.2 h, respectively (P < 0.05). Conclusion  Seven‐day administration of tenatoprazole provides a prolonged duration of acid suppression, especially during the night‐time, with little effect of food or time of dosing.